Crystal Field Splitting Energy (Δo) and Racah Parameters (B) of Some Metal-Saccharine and Metal-Saccharine-Ethylenediamine Complexes (Dhaka University Journal of Science, 2023)
[M(sac)2(H2O)4].2H2O [sac = saccharinato anion, M = Fe(II), Co(II), Ni(II), and Cu(II)], and [M(sac)2(en)2].2H2O [sac = saccharinato anion, en = ethylenediamine, M = Fe(II), Co(II), Ni(II) and Cu(II)] were prepared in an aqueous medium. The compounds are crystalline of different colors and are ambiently stable. By examining their physico-chemical properties and relevant literature, the metal(II) ions in both [M(sac)2(H2O)4].2H2O and [M(sac)2(en)2].2H2O complexes are octahedrally coordinated. In the former by four neutral H2O molecules and two monoanionic sac ligands while in later, the octahedral sites fulfilled by two neutral bidentate ethylenediamine molecules and two monoanionic sac ligands. Splitting of the crystal field (Δo) and Racah parameter (B) of two sets of complexes [M(sac)2(H2O)4].2H2O and [M(sac)2(en)2].2H2O are estimated from their electronic spectra using Tanabe-Sugano diagram of Co(II) and Ni(II) complexes while Δo values of Fe(II) and Cu(II) derivatives are calculated directly from their absorption maxima. Our experimental results show that for the studied ligands and the divalent transition metal ions, the Δo values vary according to the following order: Cu(II) > Fe(II) > Co(II) > Ni(II).Dhaka Univ. J. Sci. 71(1): 6-12, 2023 (Jan)